UNMET NEED KELUARGA BERENCANA (KB) PADA PASANGAN USIA SUBUR PENDATANG DAN LOKAL: SEBUAH STUDI KUALITATIF - Kadek Widiantari; Gusti Ayu Martha Winingsih (Medika Respati : Jurnal Ilmiah Kesehatan, 2021)
Unmet Need Family Planning  for Couples of Childbearing Age Immigrants and Locals: A Qualitative StudyBackground:the number of unmet need for family planning  in North Denpasar District is the highest compared to other sub-districts in Denpasar City. Objectives::  this study aims to determine the reasons for not using contraception among migrant and local couples of childbearing age.Methods:this study used a qualitative design with a phenomenological approach through in-depth interviews with 22 couples of childbearing age consisting of 11 local and immigrant who met the criteria for unmet need, the Head of the UPT BKKBN, North Denpasar District and the holder of the family planning program at Puskesmas III North Denpasar. PUS is selected pourposively from each village or kelurahan. Data analysis is done thematically. Results:the results of in-depth interviews showed four main themes related to the reasons for couples of childbearing age not using contraception, namely the first lack of knowledge about contraception. Second, there are negative experiences related to previous contraceptive use, both personal experiences and other people's experiences. Third, the absence of support from the partner and fourth the influence of religious and cultural beliefs. Research also shows that knowledge, experience and religious and cultural beliefs form negative perceptions towards the use of contraceptives.Conclusion:the tendency of couples of childbearing age not to use contraception is caused by several factors that form negative perceptions of the use of contraceptives and the lack of husband's support.